The Influence Of Transformational Leadership And Reward Systems On Employee Performance At Recheese Factory Kedaton Fast Food Restaurant, Bandar Lampung - Michael Alesandro; Irsandi; Agus Purnomo; Suci Asfarani (Cita konsultindo, 2026)
Transformational leadership and reward systems play an important role in improving employee performance in the fast-food restaurant industry. Inspirational leadership and fair, transparent reward systems can enhance employee motivation, commitment, and productivity. Therefore, this study analyzes the influence of transformational leadership and reward systems on employee performance at Recheese Factory Fast Food Restaurant, Kedaton, Bandar Lampung. The purpose of this study is to examine the effect of transformational leadership and reward systems on employee performance at Recheese Factory Fast Food Restaurant, Kedaton, Bandar Lampung. This research employs a quantitative approach. The population consists of all employees of Recheese Factory Fast Food Restaurant, Kedaton, Bandar Lampung, totaling 35 employees, with a sample of 35 respondents. Data analysis was conducted using multiple linear regression analysis. The results indicate that transformational leadership and reward systems have a positive and significant effect on employee performance, both individually and simultaneously, indicating that both variables are important factors in enhancing employee performance.